Layanan Pendidikan dan Pembelajaran Pada Anak Slow Learner - Tia Ivana; Depila Citra; Faizah Aulia Martini; Opi Andriani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Special programs for children with mild slow learner barriers are being formed in part by the characteristics that distinguish these children from their peers. There are marked differences in factors related to the level of intellectual development, such as the ability to process information, the ability to acquire and use language, and emotional development. There are substantial differences, too, in the strengththateachchildbringstotheirdevelopment.Adaptivebehaviorismoredifficulttoassessbecause behavior can differ depending on the environment.